THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN ENGLISH LANGUAGE LEARNING AT MADRASAH TSANAWIYAH (MTs) - Hamdani Hamdani; Absharini Kardena (Adisam Publisher, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum at Madrasah Tsanawiyah (MTs). The method used in this research is qualitative descriptive. This qualitative research collects data through observation, interviews, and documentation studies. The research objects chosen are that who understand and master the issues being studied. The subjects in this study are English teachers at MTs Rambatan, Tanah Datar Regency, West Sumatera Province. The Miles and Huberman analysis technique is used through the stages of data reduction, data presentation, and conclusion drawing. This study shows that the Merdeka Curriculum has been implemented in the planning, implementation, and evaluation stages of learning. Unlike the 2013 curriculum, the implementation of the Merdeka Curriculum at MTs Rambatan prioritizes the comfort of teachers and students by providing freedom to innovate, express, and be creative in determining active learning activities centered on students. This treatment provides implementation in creating effective learning by involving intensive student participation and appreciation so that educational goals can be achieved.